2018
DOI: 10.1111/ijfs.13936
|View full text |Cite
|
Sign up to set email alerts
|

Influence of guar gum on the baking quality of gluten‐free cheese bread made using frozen and chilled dough

Abstract: Summary The aim of the study was to assess the effect of guar gum on the quality and textural properties of gluten‐free (GF) cheese bread made using chilled and frozen GF cheese dough. The guar gum addition was at 3.5% (G3.5), 4% (G4) and 4.5% (G4.5) levels, based on the weight of the cheese in the product. Samples of frozen dough with 3.5% guar gum and of chilled dough with 4.5% guar gum were chosen for sensory analysis as they had the closest hardness and specific volume to samples of fresh dough and dough w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(90 reference statements)
0
10
0
Order By: Relevance
“…Crumb and crust moisture contents were measured in three (3) samples per treatment according to AACC 44-15.02 (American Association of Cereal Chemists, 2000). Water activity (A w ) of the crumb of two (2) samples per treatment was measured using a dew point hydrometer at 25 °C (Aqualab series 3TE, Decagon, Devices, Pullman, WA, USA) (Zapata et al, 2019).…”
Section: Quality and Textural Properties Of The Gf Cheese Breadmentioning
confidence: 99%
See 3 more Smart Citations
“…Crumb and crust moisture contents were measured in three (3) samples per treatment according to AACC 44-15.02 (American Association of Cereal Chemists, 2000). Water activity (A w ) of the crumb of two (2) samples per treatment was measured using a dew point hydrometer at 25 °C (Aqualab series 3TE, Decagon, Devices, Pullman, WA, USA) (Zapata et al, 2019).…”
Section: Quality and Textural Properties Of The Gf Cheese Breadmentioning
confidence: 99%
“…The crumb color of GF cheese bread samples was measured using a sphere spectrocolorimeter (Model SP60, X-Rite Onc., MO, USA). Four samples were taken from each treatment and the color values of crumb samples were recorded at triplicate (Zapata et al, 2019). The hardness (N), springiness, cohesiveness and chewiness (N) of GF cheese bread were assessed using a texture analyzer (TA-XT2i, Stable Micro Systems, Godalming, U.K.) equipped with a 50 kg load cell and a 100 mm diameter cylindrical aluminum probe (SMSP/100) (Rodriguez-Sandoval et al, 2017b).…”
Section: Quality and Textural Properties Of The Gf Cheese Breadmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, Xuan et al [9] demonstrated that hydroxypropyl methylcellulose could avoid the recrystallization of water to stabilize the microstructure and conformation of the gluten network. To protect the structure and properties of frozen dough, the utilization of hydrocolloids is an effective way to stabilize the quality of frozen dough and its final foods [10].…”
Section: Introductionmentioning
confidence: 99%